Leadership in Action: Lending an Ear: Why Leaders Must Learn to Listen Actively - Hoppe, Michael (Center for Creative Leadership, 2007)
The ability to listen effectively is an essential component of leadership. But many leaders, often unknowingly, fall short in this area. By learning the skills and behaviors of active listening-the willingness and ability to hear and understand-leaders can become more effective.